Bacterial Meningitis in the Absence of Cerebrospinal Fluid Pleocytosis: A Case Report and Review of the Literature - Ryota Hase; Naoto Hosokawa; Makito Yaegashi; Kiyoharu Muranaka (Canadian Journal of Infectious Diseases and Medical Microbiology)
Elevation of cerebrospinal fluid (CSF) cell count is a key sign in the diagnosis of bacterial meningitis. However, there have been reports of bacterial meningitis with no abnormalities in initial CSF testing. This type of presentation is extremely rare in adult patients. Here, a case involving an 83-year-old woman who was later diagnosed with bacterial meningitis caused by Neisseria meningitidis is described, in whom CSF at initial and second lumbar puncture did not show elevation of cell counts. Twenty-six non-neutropenic adult cases of bacterial meningitis in the absence of CSF pleocytosis were reviewed. The frequent causative organisms were Streptococcus pneumoniae and N meningitidis. Nineteen cases had bacteremia and seven died. The authors conclude that normal CSF at lumbar puncture at an early stage cannot rule out bacterial meningitis. Therefore, repeat CSF analysis should be considered, and antimicrobial therapy must be started immediately if there are any signs of sepsis or meningitis.